2020
DOI: 10.1002/advs.201902320
|View full text |Cite
|
Sign up to set email alerts
|

Novel All‐Nitrogen Molecular Crystals of Aromatic N10

Abstract: Nitrogen has unique bonding ability to form single, double, and triple bonds, similar to that of carbon. However, a molecular crystal formed by an aromatic polynitrogen similar to a carbon system has not been found yet. Herein, a new form of stable all‐nitrogen molecular crystals consisting of only bispentazole N10 molecules with exceedingly high energy density is predicted. The crystal structures and the conformation of N10 molecules are strongly correlated, both depending on the applied external pressure. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Of course, other oligomers are also possible (N 10 , N 60 ) and have been examined. [48,49] The limit of oligomers, the 1D infinite chain, was predicted to form as well. [14,15,50] In chainlike structure, nitrogen atoms are connected by alternating single and double bonds, and therefore its region of stability is predicted to be after molecular N 2 but before that of cg nitrogen.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…Of course, other oligomers are also possible (N 10 , N 60 ) and have been examined. [48,49] The limit of oligomers, the 1D infinite chain, was predicted to form as well. [14,15,50] In chainlike structure, nitrogen atoms are connected by alternating single and double bonds, and therefore its region of stability is predicted to be after molecular N 2 but before that of cg nitrogen.…”
Section: Theoretical Predictionsmentioning
confidence: 99%
“…106 Many other stable or metastable polymeric nitrogen phases at high pressures have also been predicted by CSP methods. 26,[107][108][109][110][111][112][113][114] Among the most-energetically stable phases, a phase sequence of cg-N / orthorhombic LP-Pba2 (188 GPa) 26 / bcc I-43m (263 GPa) 111 / orthorhombic Cmca (2200 GPa) 112 / tetragonal P4/nbm (2500 GPa) 112 was suggested (Fig. 5b-d).…”
Section: Polymeric Nitrogenmentioning
confidence: 99%
“…Subsequently, Michael et al showed that N crystals are dynamically metastable at room temperature by metadynamic simulations, but dissociate to N molecules above 700 K [ 22 ]. Metastable all-nitrogen molecular crystals consisting of N molecules were recently reported by Shijie Liu et al [ 23 ] The structures of these molecular crystals are affected by external pressure, and their decomposition temperature is much higher than room temperature. There is experimental evidence for the isolation of Td-N [ 18 ], although the conclusive assignment of spectral features requires further experimentation.…”
Section: Introductionmentioning
confidence: 99%